Pengaruh minat belajar terhadap kemampuan penalaran matematis siswa SMP pada materi lingkaran - Arsya Putri Khairunnisa; Fatimah Aqilah Ichtiari; Ibtisamah Laila; Rakhmah Fakhriani; Rinjania Rinjania; Dadang Juandi; Bill Chairy Rizki Bustaren (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This study examines how the learning motivation of junior high school students affects their ability to think mathematically about circles. The quantitative approach used in this study is causal-associative design. A total of 32 grade IX students from an agricultural junior high school in Bandung Regency were selected through purposive sampling techniques. Mathematical reasoning ability tests and learning interest questionnaires were distributed to them. IBM SPSS Statistics 26 was used to perform heteroscedasticity, linearity, and normality tests to analyze data using simple linear regression. The results of this study show that students' mathematical reasoning skills are positively and significantly influenced by their motivation in learning. It is hoped that this research can provide concrete evidence on how interest in learning affects mathematical thinking skills related to circular material. In addition, this research will assist educators in designing teaching methods that can arouse students' curiosity about mathematical reasoning. Future researchers are advised to collect larger samples to analyze more variables.